RELIGIOUS MODERATION IN FUNERAL CEREMONIES: A STUDY OF THE COMMUNITY OF NAGARI AIA DINGIN, SOLOK - Saskia Handayani; Rido Jamallius; Rozi Syafwan (Religi: Jurnal Studi Agama-agama, 2026)
Religious moderation has become a significant theme in socio-religious academic discourse, particularly in discussions of religious practices intertwined with local culture. Nevertheless, studies examining the implementation of religious moderation values within death rituals remain limited, especially among Minangkabau indigenous communities. This study aims to examine and interpret the values of religious moderation manifested in funeral ceremonies in Nagari Aia Dingin, Solok Regency, and to analyze their contribution to maintaining social harmony within the community. The research employs a qualitative approach using a field study method. Data were collected through participatory observation, in-depth interviews with traditional leaders, religious figures, and local community members, as well as documentation. Data analysis was conducted using a descriptive-interpretative technique through the stages of data reduction, data presentation, and conclusion drawing. The theoretical framework of this study is grounded in the theory of religious moderation, which emphasizes the principles of balance (tawassuth), tolerance (tasamuh), and justice (i‘tidal), along with an integrative perspective on the relationship between custom and religion within Minangkabau society. The findings reveal that funeral ceremonies in Nagari Aia Dingin reflect religious moderation values through mutual respect among community members, the harmonization of customary practices and Islamic law, deliberative decision-making processes, and strong social solidarity. These values function not only as religious guidelines but also as social mechanisms for preventing conflict and strengthening social cohesion. This study underscores that local traditions can serve as strategic mediums for the actualization of religious moderation at the community level. Keywords: religious moderation, funeral ceremonies, custom and religion, Minangkabau society   Moderasi beragama merupakan tema penting dalam diskursus akademik sosial-keagamaan, khususnya dalam pembahasan praktik keagamaan yang berkelindan dengan budaya lokal. Meskipun demikian, penelitian yang mengkaji penerapan nilai-nilai moderasi beragama dalam ritual kematian masih belum banyak dilakukan, terutama pada komunitas adat Minangkabau. Penelitian ini bertujuan untuk mengkaji dan menginterpretasikan nilai-nilai moderasi beragama yang terwujud dalam pelaksanaan upacara pemakaman di Nagari Aia Dingin, Kabupaten Solok, serta kontribusinya dalam menjaga keharmonisan kehidupan sosial masyarakat. Penelitian ini menggunakan pendekatan kualitatif dengan metode penelitian lapangan. Pengumpulan data dilakukan melalui observasi partisipatif, wawancara mendalam dengan tokoh adat, tokoh agama, serta masyarakat setempat, dan didukung oleh dokumentasi. Data dianalisis menggunakan teknik deskriptif-interpretatif melalui proses reduksi data, penyajian data, dan penarikan kesimpulan. Kerangka teoritik yang digunakan dalam penelitian ini adalah teori moderasi beragama yang menekankan nilai keseimbangan (tawassuth), sikap toleransi (tasamuh), dan prinsip keadilan (i‘tidal), serta pendekatan integratif antara adat dan agama dalam masyarakat Minangkabau. Temuan penelitian menunjukkan bahwa pelaksanaan upacara pemakaman di Nagari Aia Dingin mencerminkan nilai-nilai moderasi beragama melalui sikap saling menghormati antarwarga, harmonisasi antara adat dan syariat Islam, pengambilan keputusan berbasis musyawarah, serta kuatnya solidaritas sosial. Nilai-nilai tersebut berfungsi tidak hanya sebagai pedoman keagamaan, tetapi juga sebagai instrumen sosial dalam mencegah potensi konflik dan memperkuat kohesi sosial. Dengan demikian, penelitian ini menegaskan bahwa tradisi lokal memiliki peran strategis dalam mengaktualisasikan moderasi beragama di tingkat komunitas. Kata kunci: moderasi beragama, ritual pemakaman, adat dan agama, masyarakat Minangkabau